2021
DOI: 10.3390/catal11030390
|View full text |Cite
|
Sign up to set email alerts
|

Highly Graphitized Fe-N-C Electrocatalysts Prepared from Chitosan Hydrogel Frameworks

Abstract: The development of platinum group metal-free (PGM-free) electrocatalysts derived from cheap and environmentally friendly biomasses for oxygen reduction reaction (ORR) is a topic of relevant interest, particularly from the point of view of sustainability. Fe-nitrogen-doped carbon materials (Fe-N-C) have attracted particular interest as alternative to Pt-based materials, due to the high activity and selectivity of Fe-Nx active sites, the high availability and good tolerance to poisoning. Recently, many studies f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Moreover, the intensity ratio of D and G band ( I D / I G ) is a vital index to evaluate defect and graphitization degree of the carbon materials. 47 It can be calculated that the value of I D / I G of Fe/Fe 3 O 4 @NC, Fe/Fe 3 O 4 @NC (Zn-free), NC (Fe-free), Fe/Fe 3 O 4 @C (N-free) and Fe 3 O 4 @NC are 0.98, 1.05, 0.96, 1.11 and 1.01, respectively. As a consequence, the graphitization degree of Fe/Fe 3 O 4 @NC is the highest compared with other iron-containing materials, indicating that the addition of zinc nitrate and melamine obviously promotes the formation of graphitization and defect structures of carbon materials, thus endowing these catalysts with good conductivity and stability, which is conducive to improve the electron transfer efficiency in the electrocatalytic ORR process.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the intensity ratio of D and G band ( I D / I G ) is a vital index to evaluate defect and graphitization degree of the carbon materials. 47 It can be calculated that the value of I D / I G of Fe/Fe 3 O 4 @NC, Fe/Fe 3 O 4 @NC (Zn-free), NC (Fe-free), Fe/Fe 3 O 4 @C (N-free) and Fe 3 O 4 @NC are 0.98, 1.05, 0.96, 1.11 and 1.01, respectively. As a consequence, the graphitization degree of Fe/Fe 3 O 4 @NC is the highest compared with other iron-containing materials, indicating that the addition of zinc nitrate and melamine obviously promotes the formation of graphitization and defect structures of carbon materials, thus endowing these catalysts with good conductivity and stability, which is conducive to improve the electron transfer efficiency in the electrocatalytic ORR process.…”
Section: Resultsmentioning
confidence: 97%
“…The dispersion of the powder was ensured using a bath sonicator at a controlled temperature. The loading was chosen to be 0.6 mg cm –2 as used in previous works. , …”
Section: Experimental Sectionmentioning
confidence: 99%
“…Despite the economic and technological problems related to the production, transport, and storage of hydrogen, the main FCs problem is on a different aspect: the high cost due to the low kinetic of the cathode reaction, the oxygen reduction reaction (ORR), and thus, the usage of Pt-based materials as catalysts is still required. With their low cost, high availability, and good tolerance to poisoning, non-precious-metal catalysts (non-PGM) are the best known alternative to Pt. During past decades, various non-PGM catalysts were investigated: M–N–C based on M–N x sites, non-precious-metal oxide, chalcogenides, and oxynitrides . The most studied are M–N–C, and among them, the most active metal center is Fe, where iron coordinate from two to five nitrogen functional groups, and among the different types of Fe–N x ( x = 1–5), the metal porphyrin-like Fe–N 4 site is considered the most important for its ORR selectivity and activity. However, different factors need to be considered to reach good performances, including site density, carbon support hierarchical structure, surface chemistry, graphitization degree, etc. Choosing the right carbon matrix is the turning point to improve catalytic performance; in fact, the increment of the active SD is per se not enough to enhance the activity, but it is necessary to rationally design the textural and porous properties of the carbon matrix to facilitate the mass transport between micropores and the bulk solution. ,, Moreover, it has been also demonstrated that the incorporation of heteroatoms can influence the catalytic performances . The idea underlying the doping process is the capability of heteroatoms to modulate the electronic structure of the carbon plane via the delocalization of the π-electrons when pinned into the carbon framework, improving the catalyst activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen atoms not only strongly anchor individual metal centres but also modify the electronic properties of the carbon material, thus altering the catalytic activity. Ternary M−N−C materials (where, for example, M=Co or Fe), which feature atomically dispersed M centres bonded to neighbouring N atoms, have been intensely investigated as promising candidates to replace Pt in a variety of electrocatalytic reactions, such as the O 2 and CO 2 reduction reactions [3–6] . Notwithstanding the high research interest, atomically dispersed M−N−C materials have been systematically synthetized and investigated only very recently.…”
Section: Introductionmentioning
confidence: 99%